Design of high-temperature f-block molecular nanomagnets through the control of vibration-induced spin relaxation. Issue 6 (8th January 2020) - Escalera-Moreno, Luis; Baldoví, José J.; Gaita-Ariño, Alejandro; Coronado, Eugenio
Abstract : An efficient general first-principles methodology to simulate vibration-induced spin relaxation in f -block molecular nanomagnets that drastically reduces the computation time. Abstract : One of the main roadblocks that still hamper the practical use of molecular nanomagnets is their cryogenic working temperature. In the pursuit of rational strategies to design new molecular nanomagnets with increasing blocking temperature, ab initio methodologies play an important role by guiding synthetic efforts at the lab stage. Nevertheless, when evaluating vibration-induced spin relaxation, these methodologies are still far from being computationally fast enough to provide a useful predictive framework. Herein, we present an inexpensive first-principles method devoted to evaluating vibration-induced spin relaxation in molecular f -block single-ion magnets, with the important advantage of requiring only one CASSCF calculation. The method is illustrated using two case studies based on uranium as the magnetic centre. Finally, we propose chemical modifications in the ligand environment with the aim of suppressing spin relaxation.